2015
DOI: 10.1155/2015/747082
|View full text |Cite
|
Sign up to set email alerts
|

Uric Acid Levels in Normotensive Children of Hypertensive Parents

Abstract: This study evaluated uric acid concentrations in normotensive children of parents with hypertension. Eighty normotensive children from families with and without a history of essential hypertension were included. Concentrations of lipid parameters and uric acid were compared. Demographic and anthropometric characteristics were similar in the groups. Systolic and diastolic blood pressure were higher in the normotensive children of parents with hypertension without statistically significant difference (P > 0.05).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…It is generally accepted the concept that the roots of primary hypertension are present in childhood and that a family history of hypertension is an excellent predictor of high BP in adults. It this regard may be interesting the findings of two recent reports showing greater SUA levels in normotensive children and adolescents with a positive parental history of hypertension than in those with a negative one . Moreover, it was observed that lowering SUA with allopurinol or probenecid resulted in a marked BP reduction in adolescents with newly diagnosed hypertension …”
mentioning
confidence: 77%
See 1 more Smart Citation
“…It is generally accepted the concept that the roots of primary hypertension are present in childhood and that a family history of hypertension is an excellent predictor of high BP in adults. It this regard may be interesting the findings of two recent reports showing greater SUA levels in normotensive children and adolescents with a positive parental history of hypertension than in those with a negative one . Moreover, it was observed that lowering SUA with allopurinol or probenecid resulted in a marked BP reduction in adolescents with newly diagnosed hypertension …”
mentioning
confidence: 77%
“…It this regard may be interesting the findings of two recent reports showing greater SUA levels in normotensive children and adolescents with a positive parental history of hypertension than in those with a negative one. 16,17 Moreover, it was observed that lowering SUA with allopurinol or probenecid resulted in a marked BP reduction in adolescents with newly diagnosed hypertension. 11,15 In contrast to the above described clinical and experimental data, in a double-blind placebo-controlled trial, including 149 overweight or obese adults with SUA >5.0 mg/dL, lowering SUA with either probenecid or allopurinol did not change either kidney specific or systemic RAS activity.…”
mentioning
confidence: 99%
“…This finding is also supported by results from the Bogalusa Heart Study [ 13 ]. Furthermore, it has been reported that normotensive children with hypertensive parents encounter high plasma UA levels [ 19 ]. These children also have a high risk of becoming hypertensive during their adolescent years compared with children with normotensive parents [ 20 ], thereby strengthening the link between these two factors.…”
Section: Ua and Hypertension In Adolescentsmentioning
confidence: 99%